Espíritos inquietos e orgulhosos: os frades capuchos na Amazônia Joanina (1706-1751) - CARVALHO JUNIOR, Roberto Zahluth de (Universidade Federal do Pará, 2014)
The present work argues the establishment of Franciscans friars as a local power, from the nets of influence that had created and of the conflicts where these friars were involved. We look for, of this form, to understand as if they construct to the social relations between the capuchos and the secular world, relations these marked by fights born from different points of view, mainly in what it is referring to the contact with the indian, and that they allow to analyze the ultimate aspects of the missionaries as a nucleus of being able in the State of the Maranhão and Grão-Pará.